2016
DOI: 10.1097/paf.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucosal Petechial Hemorrhages (Wischnewsky Lesions), Hypothermia, and Diabetic Ketoacidosis

Abstract: For more than 100 years since their initial description, gastric mucosal petechial hemorrhages have been discovered at autopsy in cases where environmental hypothermia was determined to be the cause of death. Although these lesions are frequently seen in deaths caused by environmental hypothermia, they can also be seen in cases where hypothermia is not implicated; however, this has been seldom described. We present a series of autopsy cases where hypothermia has been conclusively ruled out as a cause of death,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…The blood identified in the gastric lumen, the only obvious morphological change, may have two explanations. Either a synergistic effect of the DKA induced acidosis, with the manifestation of coagulation disorders and subsequent hemorrhage, or the existence of a marked physiological stress often present in agonic states [12]. Wischnewsky gastric lesions and acute esophageal necrosis were also not identified in our case.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The blood identified in the gastric lumen, the only obvious morphological change, may have two explanations. Either a synergistic effect of the DKA induced acidosis, with the manifestation of coagulation disorders and subsequent hemorrhage, or the existence of a marked physiological stress often present in agonic states [12]. Wischnewsky gastric lesions and acute esophageal necrosis were also not identified in our case.…”
Section: Discussionmentioning
confidence: 54%
“…There are authors who consider Armanni-Ebstein kidney injuries as pathognomonic for DKA [9,10]. Recent studies correlate Wischnewsky gastric lesions and acute esophageal necrosis with death caused by DKA [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, differences may result from severe atrophic gastritis or Helicobacter pylori infection, which may cause a low secretion of gastric acid 31 . Wischnewski spots have been recognized in cases of non-hypothermic diabetic ketoacidosis 32 and fatal burn 33 . Nevertheless, the genesis and pathophysiology of these spots in cases of fatal hypothermia remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These lesions, as described by Wischnewsky, are expressed as "Wichnewsky spot" [26,27]. Possible causes of these stains are thought to be cellular damage caused by submucosal hypoxia, which is secondary to the shift of the oxyhemoglobin dissociation curve to the left and decrease in metabolic rate [1,6,[27][28][29]. It has been reported that the incidence of hypothermia in Wischnevsky ulcers varies between 44%-90.9% [30].…”
Section: Discussionmentioning
confidence: 99%